A hybrid approach with fuzzy logic in a multi-agent system for controlling autonomous mobile robots in known environments. (4th June 2010) - Solano-Aragon, Cinthya; Alanis, Arnulfo; Castillo, Oscar
This paper describes the development of a multi-agent system (MAS), which is supported with fuzzy logic (to control the robot's movements in a reactive path) and vision, which helps the control of an autonomous mobile robot to exit a maze. The research consists of two stages. In the first stage the problem is to be able to make the robot exit a maze, the mobile robot is positioned at the entrance (point A) and should reach an exit (B), it should be noted that we are working with a NXT Lego MINDSTORMS robot. In its second phase the problem is to make the robot search for a recognised object, for this, a camera is used to capture images, which will be processed with vision techniques, for their identification, and after that, the MAS takes the decision to evade or take the object as considered appropriate.